Do China's food safety standards affect agricultural trade? The case of dairy products. Issue 1 (2014) - Dingqiang Sun; Jikun Huang; Jun Yang
<x xml:space="preserve"> Abstract </x> Purpose – The purpose of this paper is to empirically examine how China's food safety standards affect agricultural trade in the case of dairy products. Design/methodology/approach – A gravity model is applied to quantitatively address the impacts of changing food safety standards in China in the case of its dairy imports. The paper considers the trade impacts of not only a specific hazard substance but also overall strictness of safety standards. Findings – The paper shows that changes in food safety standards of dairy products have no effect on China's dairy imports. The finding is not particularly surprising considering special characteristics of China's food safety standards. Given the fact that China's safety standards are relatively lower than that in its major exporters, the trade‐impeding effect may not be substantial. Research limitations/implications – First, this study is unable to estimate the trade‐enhancing and trade‐impending effects separately. Second, the study does not account for a potential endogeneity issue associated with food safety standards. Originality/value – This paper contributes to the debate on how food safety standards affect trade by demonstrating that safety standards in developing countries like China can affect international trade differently from that in developed countries. Although results are specific to China's dairy imports, the explanations are applicable to food safety standards in other developing countries. <ack> <x xml:space="preserve"> Acknowledgements </x> The authors acknowledge the financial support of Qinghua University (CIRS2012‐2), Chinese Academy of Sciences (KZZD‐EW‐08‐04, KSCX1‐YW‐09‐04, KACX1‐YW‐0906), the European Community (227202, NTM‐IMPACT; 044255, SSPE) and National Sciences Foundation of China (70873116). The authors would also like to thank Wenqian Yang and Kunli Li for their help in collecting the data. The authors are solely responsible for the contents of this paper. </ack>